Regulatory Policy in Korea Towards Better Regulation (OECD Reviews of Regulatory Reform, 2017)
Regulatory reform has been a top priority in Korea for several successive administrations. Maintaining momentum for reform in Korea will be essential for producing tangible results and supporting inclusive growth, productivity and innovation. The Regulatory Reform Review of Korea provides key insights into a mature regulatory system and follows two previous Regulatory Reform Reviews of Korea completed in 2000 and 2007. It identifies a number of areas where improvements could help Korea reap the full benefits of the reforms introduced so far. It stresses the need for a clear strategy for regulatory policy in order to make better use of the resources deployed.